Alternative models of rural growth and development: The case of wine production of VQPRD wine in the Naousa and Amynteon regions in Greece - Electra Pitoska; Themistokles Lazarides (European Regional Science Association (ERSA), 2010)
Quality rural products in general and wine more specifically, acquire an increasingly important role in European Communities Rural Growth policies. This results from the fact that they have a commercial advantage over other products, they support rural income and the rural economy, contribute to the protection of natural environment, retain the rural population in the countryside, encourage the development of new professional activities (like agro tourism, wine tourism e.t.c.) and bring to surface local knowledge and the cultural wealth of the Less Favoured Regions. The present paper, based on a research that was carried out in 2009, attempts to examine whether these findings apply in the Greek countryside, and more specifically at the provincial regions of Naousa and Amynteon, which are specialised in the production of VQPRD wine. The two regions (areas) present important similarities and differences as for the extent of vinicultural area, the number of wine factories, their participation in networks and the linkages of local economy and vinicultural activity. The conclusions refer to the degree of adaptation of those two regions in the alternative model of rural growth that is being promoted by the European Union
Keywords: R11; R58; 330; rural growth; development; region of origin; wine sector; Greek countryside; Naousa; Amynteon